Childhood Dystonia-Parkinsonism Following Infantile Spasms—Clinical Clue to Diagnosis in Early Beta-Propeller Protein-Associated Neurodegeneration - Hornemann, Frauke; Le Duc, Diana; Roth, Christian; Pfäffle, Roland; Huhle, Dagmar; Merkenschlager, Andreas (Neuropediatrics, 2020)
Introduction Beta-propeller protein-associated neurodegeneration (BPAN) is a very rare, X-linked dominant (XLD) inherited member of the neurodegeneration with brain iron accumulation (NBIA) disease family.Case report We present a female case of BPAN with infantile spasms in the first year, Rett-like symptomatology, focal epilepsy, and loss of motor skills in childhood. Menarche occurred at the age of 9, after precocious pubarche and puberty.Dystonia-parkinsonism as extrapyramidal sign at the age of 10 years resulted in radiological and genetic work-up.Results Burke–Fahn–Marsden Dystonia Rating Scale (BFMDRS) measured 66/120 points in body part-related dystonia symptoms. Cerebrospinal fluid examination showed dopamine depletion.T2 and B0 sequences of the diffusion-weighted magnetic resonance imaging showed susceptibility artifacts with NBIA-typical hypointense globus pallidus (GP) and substantia nigra (SN). Next-generation sequencing revealed a BPAN-causing pathogenic variant in WDR45 (WD repeat-containing protein 45) gene (c.830 + 1G > A, XLD, heterozygous, de novo). Skewed X-inactivation was measured (2:98).Conclusions Autophagy-related X-linked BPAN disease might still be underdiagnosed in female cases of infantile spasms.Skewed X-inactivation will have mainly influenced the uncommon, very early childhood neurodegenerative symptomatology in the present BPAN case. Oral levodopa substitution led to improvement in sleep disorder, hypersalivation, and swallowing.Reduced white matter and hypointense signals in SN and GP on susceptibility sequences in magnetic resonance imaging are characteristic radiological findings of advanced disease in NBIA. No BPAN-typical halo sign in T1-weighted scan at midbrain level was seen at the age of 11 years. NBIA panel is recommended for early diagnosis.
Keywords: BPAN; parkinsonism; WDR45; neurodegeneration; dopamine; infantile spasms